Structures of Cyclic Organosulfur Compounds From Garlic (Allium sativum L.) Leaves - Fukaya, Masashi; Nakamura, Seikou; Hayashida, Hitoshi; Noguchi, Daisuke; Nakashima, Souichi; Yoneda, Taichi; Matsuda, Hisashi (Frontiers in Chemistry, 2020)
Five new cyclic organosulfur compounds, foliogarlic disulfanes A1 (1), A2 (2) and A3 (3), and foliogarlic trisulfane A1(4) and A2 (5) were isolated from the leaves of Allium sativum (garlic). The chemical structures of these compounds were elucidated on the basis of physicochemical evidence. Compounds 1-5 were obtained as complex compounds with di- or tri-sulfane and tetrahydro-2H-difuro[3,2-b:2',3'-c]furan-5(5aH)-one. In addition, the hypothetical synthetic pathways of these compounds were suggested.